„Grafika komputerowa” – nauczyciel i uczeń w cyfrowym świecie obrazów. Notatki pedagogiczne - Materne , Agnieszka (Studia Edukacyjne, 2023)
In the era of visual culture, the reception and creation of images becomes an inseparable element of everyday life. Unfortunately, as research shows, both students and teachers suffer from a shortage of skills related to the creation of graphic messages legible in the form (aesthetic) and content. Despite the hypertectuality of the young generation, they also appear as digital immigration as defined by Prensky. In this paper, I focus on indicating the theoretical and historical foundations of computer graphics and its types, i.e. raster and vector graphics. In school practice, both of these graphic areas are poorly understood and often used inadequately (or not at all, e.g. vector graphics) for didactic needs. Getting to know the graphic software and its capacities will allow both teachers and students to function adequately to the digital times and will sensitize them to the possible visual manipulation of reality, i.e. presenting lies as truth, half-truth or “true facts” that often cause extreme emotional reactions.